2012
DOI: 10.1371/journal.pone.0040980
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Relationships between Cholinergic Tone, Synchronous Bursting and Synaptic Remodeling

Abstract: Cholinergic neuromodulation plays key roles in the regulation of neuronal excitability, network activity, arousal, and behavior. On longer time scales, cholinergic systems play essential roles in cortical development, maturation, and plasticity. Presumably, these processes are associated with substantial synaptic remodeling, yet to date, long-term relationships between cholinergic tone and synaptic remodeling remain largely unknown. Here we used automated microscopy combined with multielectrode array recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(80 citation statements)
references
References 77 publications
(106 reference statements)
14
59
0
Order By: Relevance
“…Pulsed ACh applications effectively suppress network synchrony, but synchrony eventually reemerges Under baseline conditions, and in agreement with many reports [27,[30][31][32][33][34][35][36]70], spontaneous activity in the cortical networks used here occurs as periods of synchronous, network-wide bursting activity which lasts for several hundreds of milliseconds, separated by longer periods (1 to 10 seconds) of near-complete quiescence or sparse, asynchronous action potentials ( Figure 2a). As mentioned in the introduction, these network activity patterns share many similarities with the forms of synchrony observed in vivo under regimes of low neuromodulatory levels.…”
Section: Rational and Experimental Approachsupporting
confidence: 91%
See 4 more Smart Citations
“…Pulsed ACh applications effectively suppress network synchrony, but synchrony eventually reemerges Under baseline conditions, and in agreement with many reports [27,[30][31][32][33][34][35][36]70], spontaneous activity in the cortical networks used here occurs as periods of synchronous, network-wide bursting activity which lasts for several hundreds of milliseconds, separated by longer periods (1 to 10 seconds) of near-complete quiescence or sparse, asynchronous action potentials ( Figure 2a). As mentioned in the introduction, these network activity patterns share many similarities with the forms of synchrony observed in vivo under regimes of low neuromodulatory levels.…”
Section: Rational and Experimental Approachsupporting
confidence: 91%
“…Indeed, in a prior study [35] we found that the chronic, prolonged (many hour) exposure of networks of cultured cortical neurons to a cholinergic agonist is associated with the gradual growth of excitatory synapses and, intriguingly, to the gradual reemergence of synchrony (see also [36]). If neuronal networks adapt to neuromodulatory input, it might be asked how the necessity to suppress network synchrony is ultimately addressed, in particular given that this activity form seems to be incompatible with attentive states and arousal [66,67].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations